PENGARUH PENGETAHUAN KEWIRAUSAHA DAN MOTIVASI WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA UNIVERSITAS PASIFIK MOROTAI - Ardin Umar, Ardin; Sibua, Nurhimah; Yuliana, Yuliana; Hasan, Jamiludin; Septiana Rustam, Irta (PT. ANAN PUBLISHER CENDEKIA, 2024)
This is study aims to determine the influence of (1). Enterpreneurial knowledge on the entrepreneurial interest of students at Morotai Pacific University, and (2). Entrepreneurial motivation on entrepreneurial interest in Morotai Pacific University students. This research is survey research. The population in this study was 50 students of Morotai Pacific University. This sampling technique was purposive sampling. Thus research used quantitative research and data ab=nalyze by using SPSS V. The results show that (1). Entrepreneurship knowledge has a positive influence on entrepreneurial interest in Morotai pacific University students by showing the regression equation y= 3,229+ 0,777 X1 calculated value of 4,367 with a significance value of 0,000 smaller than 0,05 and a regression coefficient value of 0,555, the more entrepreneurial knowledge obtained, the more entrepreneurial interest will be fostered in Morotai Pcific Universty Students. (2). Entrepreneurial Motivation has a positive influance on entrepreneurial interest in Morotai Pacific University students as shown by the regression equation y= 3, 229 + 0, 380 X2-.This can be proven by a calculated value of 4,065 with a significant value of 0,000 smaller than 0,05 and has a regression coefficient value of 0, 380. The more Entrepreneeuiral Motivation obtained, the more Entrepreneurial Interrest will grow in Morotai Pacfic University students.